Himalayan mobilities : an exploration of the impact of expanding rural road networks on social and ecological systems in the Nepalese Himalaya - Beazley, Robert E.; Lassoie, J. P. (Springer, 2017)
The goals of this book are to update information on the effects of rural road development, both in Nepal and globally, explain the environmental, socioeconomic, and sociocultural impacts of expanding rural road networks in the Nepalese Himalaya, and to promote further studies on rural road development throughout the world based on studies and investigations performed in Nepal. Readers will learn about the history of rural road development, as well as the challenges to effectively design and construct rural roads and how these obstacles may be overcome. Chapter one offers a global review of road development, and both the positive and negative impacts of rural road implementation. Chapter two defines mobilities within the context of coupled social and ecological systems, specifically in the Nepalese Himalaya. Chapters three through five detail the environmental, socioeconomic, and sociocultural impacts expanding rural road networks through several case studies. The concluding chapter summarizes the findings of the book, discussing the need for interdisciplinary cooperation and collaboration to avoid negative consequences. This book will be of interest to teachers, researchers, policy makers, and development organizations.
Keywords: Rural roads -- Social aspects -- Nepal.; Rural roads -- Environmental aspects -- Nepal.; Nepal.; elektronické knihy; electronic books